Eight-Year Follow-Up Using a Fresh Osteochondral Allograft for a Femoral Head Chondroblastoma in a 17-Year-Old Patient - Louis-Charles Moreau; Philippe Beauchamp-Chalifour; Etienne L. Belzile; Norbert Dion (Case Reports in Orthopedics)
Chondroblastoma is a rare benign tumor that affects the epiphysis of long bones in adolescents. Chondroblastoma located in the femoral head is associated with a higher recurrence rate and carries the additional risks of head collapse and degenerative hip disease. Aggressive curettage followed by bone grafting is the current mainstay of treatment. To our knowledge, the long-term postoperative outcome of this technique remains unknown due to the short follow-up of previous case reports. We present the case of a 17-year-old male who underwent fresh osteochondral allograft following curettage of a femoral head chondroblastoma, using a Ganz surgical hip dislocation. He made an uneventful recovery without tumor recurrence. The patient was followed up to 8 years postoperatively. However, there were clinical and radiographic degenerative changes at 6 years of follow-up.